One Undertaking, Multiple Entities: The Evolving Legal Framework of Corporate Group Liability in EU Competition Law - Osmanovic,Dalila (2025)
This thesis investigates the evolving framework of corporate group liability in EU competition law, with a focus on the economic unit doctrine under Article 101 TFEU. It analyses how competition liability can extend beyond traditional parent-subsidiary relationships to include various entities within a corporate group. Central to this analysis is the Akzo Nobel presumption, which assumes that a parent company owning nearly all of a subsidiary's shares exerts decisive influence and can thus be held jointly liable for competition infringements. The study outlines the legal, structural, and functional mechanisms through which decisive influence is established and examines the evidentiary challenges of rebutting the presumption of decisive influence. It also considers situations where liability is based not on formal ownership but on actual control, such as in joint ventures or minority shareholdings. Two landmark cases, Sumal and Athenian Brewery, are analysed in depth. Sumal introduced the concept of downward liability, allowing victims to bring claims against subsidiaries for infringements committed by parent companies, provided they form part of the same economic unit. Athenian Brewery further extended the doctrine's procedural reach by confirming that jurisdiction under the Brussels I bis Regulation can be grounded in the presumption of decisive influence. The thesis explores the broader implications of these developments for both public and private enforcement, including strengthened deterrence, expanded access to private damages, and emerging jurisdictional challenges. However, it also identifies unresolved issues, particularly concerning the liability of sister companies and the jurisdictional issues that arise in such contexts. In sum, this research underscores the economic unit doctrine’s critical role in modern antitrust enforcement, its practical challenges, and its potential future evolution in an increasingly interconnected corporate world.
Keywords: economic unit; liability; subsidiary liability